Antipsychotics, Metabolic Adverse Effects, and Cognitive Function in Schizophrenia - MacKenzie, Nicole E.; Kowalchuk, Chantel; Agarwal, Sri Mahavir; Costa-Dookhan, Kenya A.; Caravaggio, Fernando; Gerretsen, Philip; Chintoh, Araba; Remington, Gary J.; Taylor, Valerie H.; Müeller, Daniel J.; Graff-Guerrero, Ariel; Hahn, Margaret K. (Frontiers in Psychiatry, 2018)
Cognitive impairment is a core symptom domain of schizophrenia. The effect of antipsychotics, the cornerstone of treatment in schizophrenia, on this domain is not fully clear. There is some evidence suggesting that antipsychotics may partially improve cognitive function, and that this improvement may vary depending on the specific cognitive domain. However, this research is confounded by various factors such as age, duration/stage of illness, medication adherence, and extrapyramidal side effects that complicate the relationship between antipsychotics and cognitive improvement. Furthermore, antipsychotics – particularly the second generation, or ‘atypical’ antipsychotics – can induce serious metabolic side effects, such as obesity, dyslipidemia and type 2 diabetes, illnesses which themselves have been linked to impairments in cognition. Thus, the inter-relationships between cognition and metabolic side effects are complex, and this review aims to examine them in the context of schizophrenia and antipsychotic treatment. The review also speculates on potential mechanisms underlying cognitive functioning and metabolic risk in schizophrenia. We conclude that the available literature examining the intersection of antipsychotics, cognition, and metabolic effects in schizophrenia is sparse, but suggests a relationship between metabolic comorbidity and worse cognitive function in patients with schizophrenia. Further research is required to determine if there is a causal connection between the well-recognized metabolic adverse effects of antipsychotics and cognitive deficits over the course of the illness of schizophrenia, as well as to determine underlying mechanisms. In addition, findings from this review highlight the importance of monitoring metabolic disturbances in parallel with cognition, as well as the importance of interventions to minimize metabolic abnormalities for both physical and cognitive health.